IMPLEMENTASI KEBIJAKAN KARTU IDENTITAS ANAK (KIA) PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BULUKUMBA (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
This thesis discusses the implementation of the child identity card policy at the Population and Civil Registration Service of Bulukumba Regency. The aim of this research is to describe and analyze the implementation of KIA in Bulukumba Regency. The method used in this research is a qualitative descriptive research method. The research results show that the implementation of the KIA policy by the Population and Civil Registration Service of Bulukumba Regency has gone quite well in terms of several indicators, namely: (1) communication; has made significant efforts in socializing KIA policies, (2) resources; resource preparation has been carried out well, (3) disposition; high commitment and enthusiasm from related parties is clearly visible and (4) bureaucratic structure; which have been properly regulated carry out an important role in carrying out the duties of the Population and Civil Registration Service. This research provides valuable insights for stakeholders in efforts to increase the effectiveness of KIA policy implementation in Bulukumba Regency.